The effects of occupational disruption during COVID-19 lockdowns on health: a cross-sectional study - Muriithi,Bernard Austin Kigunda; Bay,R. Curtis (PeerJ, 2024)
The disruption in daily activity performance during COVID-19 lockdowns is widely understood to have impacted health, but a better understanding of how restricted performance of specific activities are associated with health is needed. This cross-sectional study answers the following question: How were changes in the performance of 16 daily activities associated with health during COVID-19 lockdowns? A total of 116 participants completed an online survey rating their health before and during COVID-19 lockdowns and comparing their recollection of the performance of 16 activities before COVID-19 with their performance during lockdowns. Multiple stepwise linear regression analysis was used to estimate the relationship between self-reported changes in activities during lockdowns and concurrent (during-lockdown) health status, while controlling for pre-COVID-19 health status. Only changes in activities that were uniquely and significantly associated with lockdown health status were retained in the final model. Health before COVID-19 accounted for 3.7% (P = 0.039) of the variance in health during COVID-19 lockdowns. After controlling for health before COVID-19, five types of activity were significantly and uniquely predictive of health during lockdowns, together accounting for 48.3% of the variance. These activities and the variances they accounted for were rest and sleep (29.5%, P < 0.001), play and recreational activities (8%, P < 0.001), work (4.8%, P = 0.002), personal hygiene (3.2%, P = 0.01), and healthy eating (2.8%, P = 0.013). The study suggests that these five types of activity should be prioritized in policy or interventions when participation in activity is constrained by lockdowns or comparable factors.
Keywords: COVID-19; Occupational disruption; Daily activities; Occupational therapy; Resilience; Quality of life; Physical health; Mental health; Social well-being; Occupational resilience